Analysis of sex steroids in human tears using LC-MS and GC-MS: Considerations and developments to improve method sensitivity and accuracy. (December 2022) - Phan, Minh Anh Thu; Gibson, Emma; Golebiowski, Blanka; Stapleton, Fiona; Jenner, Andrew M.; Bucknall, Martin P.
Abstract: Sex steroids play a role in regulation of tear film function and may exert their action locally at the ocular surface. However, measurement of sex steroids in tears is difficult due to small-volume tear samples and very low concentrations of the hormones. This short communication highlights what has been achieved to date in the analysis of tear sex steroids using ultra-performance LC-MS (UPLC-MS) as previously published, and reports further and more recent investigations toward optimising mass spectrometry method sensitivity and accuracy. The published UPLC-MS method successfully measured progesterone, androsterone glucuronide and 5α-androstane-3α, 17β-diol in pooled basal tears of postmenopausal women, and fourteen sex steroid standards in methanol. Limitations included sub-optimal limits of detection (LOD) and lower limits of quantification (LLOQ) for some analytes (particularly oestrogens), exclusion of sample matrix effects and no use of internal standards. This update reports on further experiments carried out to improve sensitivity and accuracy. Sample matrix effects, internal standard spiking, and derivatisation with dansyl chloride and oximes were investigated. Dansylation significantly improved the LOD and LLOQ of oestrogens and their metabolites, by a factor of 10 for oestradiol and a factor of 5 for oestrone, but sensitivity of this updated method is not sufficient however for analysis of these oestrogens in human tears. Using gas chromatography-mass spectrometry (GC-MS) as an alternative technique to LC-MS, improved sensitivity for derivatised oestradiol is reported. This work demonstrates the need to develop higher sensitivity methods and points researchers towards specific MS ionisation techniques for future analysis of sex steroids in tears, in order to progress current understanding of the role of sex steroids in tear function and dry eye. Highlights: Analysis of sex steroids in tears is challenging due to the extremely limited sample volumes and low analyte concentrations. UPLC-MS performed on a Orbitrap MS in APCI+ mode with dansyl chloride derivatisation improved sensitivity for oestrogens. UPLC-MS plus derivatisation was more suitable than GC-MS for analysing sex steroids in tears.